Os impactos do fim do CAME sobre a sociedade pós-revolucionária cubana e o socialismo na ilha - Jurca, Américo Cruz Neto (2004)
The historical circumstances in which Cuban Revolution took place, at the clímax of the Cold War, besides Cuba’s geographic position and its singular relationship with the United States, were decisive to its aproach to the soviet field.With the ruin of the so called “real socialism” and the end of CAME, Cuba was suddenly deprived of the conditions that were essencial to its survival as a country that seeks development in a socialist basis.The crises of the nineteen eighties did not make Cuba to give up the socialist ideal, and the country now undertakes an strategical retreat , opening its economy to the capitalist world and giving more room for market relations.Cuban economy basically remains under a regime of State property and is still, to a great extent, centrally planned.Despite the reforms and the increasing use of monetary and trade relations , government authorities declare firmly its intent of keeping on improving the socialist trend.